Identification of Dyestuffs in the Natural Pigments Produced with Al3+, Fe2+ and Sn2+ Mordant Metals from Cochineal (Dactylopius coccus Costa) and Walloon oak (Quercus ithaburensis Decaisne) by HPLC-DAD - Deveoglu, O.; Torgan, E.; Karadag, R. (Asian Journal of Chemistry, 2010)
In this study, the natural pigments from the cochineal (Dactylopius coccus Costa) dye insect and the walloon oak (Quercus ithaburensis Decaisne) dye plant were produced by using KAl(SO4)2·12H2O (alum), FeSO4·7H2O and SnCl2·2H2O mordants. A reversed-phase high performance liquid chromatography (HPLC) with diode array detection (DAD) method was utilized for the identification of dyestuffs in the natural pigments. The dyestuff extractions from the pigments were carried out with HCl/MeOH/H2O (2:1:1; v/v/v) solution.